Can formate dehydrogenase from Candida boidinii catalytically reduce carbon dioxide, bicarbonate, or carbonate to formate?. (13th May 2020) - Sato, Ryohei; Amao, Yutaka
Abstract : It was found that CbFDH was catalytically reduce only carbon dioxide to formate among the three types of carbonate species, carbon dioxide, bicarbonate and carbonate for the first time. Abstract : Formate dehydrogenase from Candida boidinii (CbFDH) reversibly catalyzes formate to carbon dioxide with the redox couple NAD + /NADH. There have been many studies on CbFDH-catalyzed oxidation of formate to carbon dioxide in the presence of NAD + . On the other hand, there are few studies on the detailed mechanism of the carbon dioxide reduction to formate catalyzed by CbFDH in the presence of NADH. In addition, it is not clear whether CbFDH can reduce carbon dioxide, bicarbonate or carbonate to formate. In this study, formate production with CbFDH in the presence of NADH was investigated in solutions with different ratios of carbon dioxide, bicarbonate and carbonate. The reaction rate of formate production with CbFDH increased in proportion to the concentration of carbon dioxide in the reaction solution. On the other hand, the formate production with CbFDH was suppressed in proportion to the concentration of bicarbonate or carbonate in the reaction solution. Thus, CbFDH was found to catalytically reduce only carbon dioxide to formate among the three types of carbonate species.